Critical pedagogy, Islamisation of knowledge and Muslim education - Hussien, Suhailah (IIUM Press, 2007)
This study attempts to reconstruct Western critical pedagogy from an Islamic perspective and to explore its contribution to the resolution of the crisis in the Muslim mind and Islamic education. It analyses the underlying assumptions behind critical theory, compares it with the Islamic philosophy of education, and with the Islamization of Knowledge project, reconstructs the Western critical pedagogy and uses the arguments of the Muslim scholars to justify for the need of critical pedagogy in Muslim education. It is argued than an Islamised critical pedagogy can offer an adequate resolution to the crisis in the Muslim mind.